Norma terapêutica da diabetes mellitus tipo 2 - Pinto, Daniel (2011)
Clinical guidelines have the potential to increase health gains, but also to cause harm. In this opinion article we state some misgivings about the application of the Portuguese National Health Directorate's guideline type 2 diabetes therapy: metformin in primary care. We seek to highlight guideline wording that may allow for multiple interpretations (alternatives to monotherapy with metformin, hierarchy of drugs to be associated with metformin, and metformin contraindications). Furthermore, we argue that it seems that choosing a glycemic target of 6.5% in a normative document to be applied in the general population may have unforeseen consequences.